THE ROLE OF THE TEACHER AS CLASS MANAGER IN INCREASING SPIRITUAL INTELLIGENCE THROUGH THE IMPLEMENTATION OF CLASSIC VALUES - Jariyah, Umi; Mujiburrohman, M (Proceeding of International Conference of Islamic Education, 2023)
This study aims to determine the role of the teacher as class manager in increasing spiritual intelligence. Qualitative research methods with a descriptive approach. The subjects of the study were 7 teachers in the MIM Bendo special program. Data collection techniques with interviews, observation and documentation. The data validation technique uses triangulation. While the data analysis uses data reduction, data presentation, and drawing conclusions. The results of this study indicate that: The teacher's role as class manager can improve students' spiritual intelligence through moral development strategies, moral studies, congregational prayers, Al-Quran learning, and Ramadhan Islamic boarding schools activities. With these steps, teachers can improve students' spiritual intelligence through fostering faith and morals. While the obstacles in increasing students' spiritual intelligence, such as a curriculum that focuses on academic aspects, lack of understanding and support, time constraints, differences in beliefs and values, and personal disobedience. To overcome these obstacles, teachers can take steps such as revising the curriculum, holding additional training, integrating spiritual values in learning, respecting students' different beliefs, and involving parents. Implementation of the teacher's role as class manager can be done